Kekerasan digital pada jurnalis perempuan di media feminis indonesia: studi kasus pada konde.co dan magdalene.co (Faculty of Communications Science, Dr. Soetomo University, 2022)
The Alliance of Independent Journalists (AJI) recorded 2020 as the year with the most cases of violence, and expanded into the digital realm. In 2020, two Indonesian feminist media, namely Konde.co and Magdalene.co experienced digital-based violence at the same moment. At that time, Konde.co experienced a Twitter account hack, and Magdalene.co experienced a ddos attack on its website. This study aims to describe digital violence in the digitalization era for female journalists, and can provide concrete examples as a form of digital violence that occurs to someone who has a dual status, namely as a woman and a journalist.